2021
DOI: 10.1128/jvi.00925-21
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon Promotes Humoral Immunity in Viral Vector Vaccination

Abstract: Recombinant viral vectors are an important platform for vaccine delivery. Our recent study has demonstrated distinct innate immune profiles in responding to viral vectors of different families (e.g., adenovirus vs. poxvirus): while human Ad5 vector is minimally innate immune stimulatory, the poxviral vector ALVAC induces strong innate response and stimulates type-I IFN and inflammasome activation. However, impact of the innate immune signaling on vaccine-induced adaptive immunity in viral vector vaccination is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…As poxviruses replicate their DNA genomes in the cytoplasm, they must avoid detection by a number of DNA sensors. It has been demonstrated that MVA triggers an antiviral response in several human and mouse cell types in a cGAS-and STING-dependent manner [32][33][34][35]. This is in agreement with the absence of multiple viral immunomodulators in the virus as a result of multiple genomic alterations that occurred during its extensive passage in avian cells.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…As poxviruses replicate their DNA genomes in the cytoplasm, they must avoid detection by a number of DNA sensors. It has been demonstrated that MVA triggers an antiviral response in several human and mouse cell types in a cGAS-and STING-dependent manner [32][33][34][35]. This is in agreement with the absence of multiple viral immunomodulators in the virus as a result of multiple genomic alterations that occurred during its extensive passage in avian cells.…”
Section: Discussionsupporting
confidence: 67%
“…Poxin is highly conserved in orthopoxviruses (OPXV) but it is inactivated in MVA [29,30]. Whilst viruses carrying poxin effectively prevent STING activation, MVA infection of human and mouse cells results in strong induction of IFN and pro-inflammatory cytokines that is dependent on cGAS and STING [31][32][33] that is crucial for the establishment of cytotoxic T cell responses and memory T cell formation [34,35]. The cGAS/STING axis is therefore essential for the antiviral response against MVA.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, these transcriptional changes lead to a coordinated and sustained anti-tumor immune response across multiple cell types ( 17 ). In addition, type I IFN is a potent adjuvant for inducing primary Ab responses ( 18 , 19 ) and plays an essential role in linking innate and adaptive immunity ( 20 ). In the context of tumoral immunity, type I IFNs can inhibit tumor cell survival, suppress angiogenesis, and stimulate the activity of T, natural killer, and dendritic cells (DCs).…”
Section: Introductionmentioning
confidence: 99%
“…The upregulated DEGs in CD16 + monocytes in the 2V7 and 2V14 groups were enriched in “type I interferon production”, “positive regulation of cytokine production”, “response to interferon gamma”, “toll-like receptor signaling pathway” and “antigen processing and exogenous antigen” pathways ( Figure 2 E, F). Notably, type I interferon signalling promotes humoral immunity following vaccination, including vaccine-induced antibody, B cell and follicular helper T (Tfh) cell responses [ 33 ]. Additionally, we analyzed the expression of type I interferon production-related pathway in innate immune cells across four time points.…”
Section: Resultsmentioning
confidence: 99%